Use of tilapia, Oreochromis mossambicus, for the control of mosquito breeding in water storage tanks in the Jaffna district of Sri Lanka - Surendran, S.N.; Kajatheepan, A.; Jude, P.J.; Ramasamy, R. (The Japanese Society of Tropical Medicine, 2008)
Mosquito-borne diseases such as dengue, chikungunya and malaria are of public health importance in Jaffna district. The use of larvivorous fish is perceived as an environmentally sound measure to control mosquitoes. A pilot study in the laboratory and field using Oreochromis mossambicus was carried out to evaluate its potentiality to control Aedes and Anopheles larvae. In the laboratory studies, O. mossambicus showed a greater feeding affinity for Aedes than either Anopheles or artificial fish diet, with a predatory index of 239.7 for Aedes, the fish having 2.9 g body weight. In the field trial, the introduction of O. mossambicus into water storage tanks proved to be effective in eliminating Aedes larvae within 3 days.
Keywords: Aedes aegypti; Anopheles subpictus; Jaffna; Larvivorous fish; Mosquito control; Oreochromis mossambicus; Sri Lanka; Water storage tanks